2020
DOI: 10.1007/s40839-020-00095-6
|View full text |Cite
|
Sign up to set email alerts
|

Religious affect and personal happiness: are there significant differences between Catholic adolescents in the Republic of Ireland and in Northern Ireland?

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…If we place this result against the findings from Theme 1, it is interesting to note that while 87% said they believe in God, 95% of the same group said that they belonged to the Catholic denomination. In other words, c. 8% of participants say they are Catholic but do not believe in God, echoing the findings of Francis et al (2019). They found that of the 16-19 year olds in Ireland who identified as Catholic, 44% were either uncertain that God exists or fairly sure God does not exist or completely confident that God does not exist.…”
Section: Theme 2: Images and Understandings Of Godmentioning
confidence: 55%
See 1 more Smart Citation
“…If we place this result against the findings from Theme 1, it is interesting to note that while 87% said they believe in God, 95% of the same group said that they belonged to the Catholic denomination. In other words, c. 8% of participants say they are Catholic but do not believe in God, echoing the findings of Francis et al (2019). They found that of the 16-19 year olds in Ireland who identified as Catholic, 44% were either uncertain that God exists or fairly sure God does not exist or completely confident that God does not exist.…”
Section: Theme 2: Images and Understandings Of Godmentioning
confidence: 55%
“…Over two-thirds saw their grandparent(s) at least once a week and 88% had a close relationship with at least one grandparent. Francis et al (2019) note that 90% of those who cite their religious identity as being important to them recognise that religion is also important to their grandparents and see them as vital in the passing on of faith. It is not surprising, then, that almost 25% of respondents in this study cited their grandparents as having a significant influence on their religious identity, with comments such as 'My grandparents go to mass every day and they go every Sunday, so they always influenced me' (Student 14).…”
Section: Theme 2: Images and Understandings Of Godmentioning
confidence: 99%
“…Their study reported a significant positive correlation between religious affect and personal happiness. In their recent review of subsequent research building on this foundation study, Francis et al (2020a) identified studies employing the same two instruments amongst seven further samples that all confirmed the finding from the original study: 212 undergraduate students in the United States of America (Francis & Lester 1997), 295 individuals ranging in age from late teens to late 70s in England (Francis & Robbins 2000), 994 secondary school students aged 15-16 years in England , 496 members of the University of the Third Age in England , 456 undergraduate students in Wales , 89 undergraduate students in Wales (Francis, Robbins & White 2003) and 3848 students aged 16-19 years in the Republic of Ireland (Francis & Lewis 2016).…”
Section: Empirical Theology and Positive Psychologymentioning
confidence: 99%
“…Recent decades have seen culture and society in both jurisdictions embrace a greater diversity and plural reality as has been seen elsewhere (Kieran 2019;Anderson, Byrne, and Cullen 2016). The separate provision for Catholic and Protestant students in schools, and the growing need to provide for those of other religions and worldviews has created a notable challenge to the school systems, North and South (Francis et al 2020;Byrne 2018;Coll 2013).…”
Section: Introductionmentioning
confidence: 96%